Hemangioma and propranolol. Some remarks at the end of treatment. Differences from corticosteroids. - Laforgia, N.; Milano, A.; De Leo, E.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
23 cases of hemangioma treated with oral propranolol at a dosage of 2 mg/kg per day were reported. 11/23 cases stopped treatment and were monitored for an average period of three months after drug withdrawal. Propranolol was as effective as corticosteroids in blocking the growth of hemangioma and in causing a significant reduction both of the size and color of hemangioma. These effects, however, seem less permanent as compared with those ones caused by corticosteroids, requiring a longer duration of treatment -7 months on average-. Apart from heart contraindications, however rare, bronchospasm, which is frequent at this age, but more often inflammatory than muscular, is not an absolute contraindication to the usage of the drug. Hypoglicemia is the most dangerous side effect of propranolol.